Early-Responding Civil Society and a Late Coming State: Findings from Turkey during the Pandemic - DOĞAN, ERHAN (WALTER DE GRUYTER GMBH, 2021)
By building on available literature and interview notes with the NGOs working mainly on refugees and irregular migrants, this study examines the experiences of civil society in Turkey in the first 6 months of the COVID-19 pandemic. One of the main findings is that NGOs responded quite early and with agility to the sufferings of people before the state entered into the field and implemented its own rules and methods to deal with the crisis. The study also reveals that the pandemic affected the focus of the NGOs, their services, finances, and working methods in the field. The organizations we examined adapted to a new online working environment which increased demand for their services and aggravated difficulties in assuring clients access to needed healthcare services. The study finds that relations with the local and central governments remain difficult, and during the pandemic, the NGOs were compelled to act very cautiously. While suffering from their society's political polarization, they report that xenophobia continues to rise and has been worsened by the impact of the pandemic.
Keywords: civil society; Turkey; COVID-19; NGOs; migrants' access to healthcare; polarization; xenophobia; digitalization